Approaches to Manipulate Ephrin-A:EphA Forward Signaling Pathway - Sarah Baudet; Johann Bécret; Xavier Nicol (MDPI AG, 2020)
Erythropoietin-producing hepatocellular carcinoma A (EphA) receptors and their ephrin-A ligands are key players of developmental events shaping the mature organism. Their expression is mostly restricted to stem cell niches in adults but is reactivated in pathological conditions including lesions in the heart, lung, or nervous system. They are also often misregulated in tumors. A wide range of molecular tools enabling the manipulation of the ephrin-A:EphA system are available, ranging from small molecules to peptides and genetically-encoded strategies. Their mechanism is either direct, targeting EphA receptors, or indirect through the modification of intracellular downstream pathways. Approaches enabling manipulation of ephrin-A:EphA forward signaling for the dissection of its signaling cascade, the investigation of its physiological roles or the development of therapeutic strategies are summarized here.